Sensitization of Cancer Cells for Chemo/Immuno/Radio-therapy - Bonavida, Benjamin; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Cancer chemotherapy can be traced back to the 1940’s and since then the world has witnessed the discovery and the important application of several new drugs. The successes of combination chemotherapy suggested that all cancers can be treated provided that the correct combination of drugs at the correct doses and correct intervals are established. However, with time, tumor cells develop mechanisms of resistance to apoptosis and no longer respond to the majority of cytotoxic therapies. Sensitization of Cancer Cells for Chemo/Immuno/Radio-therapy, edited by Benjamin Bonavida, reviews novel approaches developed to reverse tumor cell resistance to chemo/immuno/radio-therapy and the use of various sensitizing agents in combination with various cytotoxics. Such sensitizing agents target gene products that regulate resistance and therefore identify novel targets for drug development. This book also introduces several of the current approaches that have been developed by established investigators in the field that are aimed at overcoming resistance. This book is the first that compiles studies on tumor cell sensitization and is useful for students, scientists, clinicians and pharmaceutical companies.
Sensitization via Membrane-Bound Receptors -- Sensitization of Epithelial Cancer Cells with Human Monoclonal Antibodies -- Targeting the Transferrin Receptor to Overcome Resistance to Anti-Cancer Agents -- Chemo-Immunosensitization of Resistant B-NHL as a Result of Rituximab (anti-CD20 mAb)-Mediated Inhibition of Cell Survival Signaling Pathways -- Agents that Regulate DR5 and Sensitivity to TRAIL -- Proteasome Inhibition: Potential for Sensitization of Immune Effector Mechanisms in Cancer -- Sensitization via Inhibition of Cell Survival Pathways (Excluding Apoptotic Signaling Pathways) -- Angiogenesis Inhibitors as Enabling Agents for the Chemotherapeutic Treatment of Metastatic Disease -- Targeting Survival Cascades Induced by Activation of Ras/Raf/MEK/ERK and PI3K/Akt Pathways to Sensitize Cancer Cells to Therapy -- Histone Deacetylase Inhibitors and Anticancer Activity -- Eicosanoids and Resistance of Cancer Cells to Chemotherapeutic Agents -- Sensitization via Transcription Factors -- The RKIP and STAT3 Axis in Cancer Chemotherapy: Opposites Attract -- Targeting Transcription Factors with Decoy Oligonucleotides: Modulation of the Expression of Genes Involved in Chemotherapy Resistance of Tumor Cells -- p53 Inhibitors as Cancer Sensitizing Agents -- Nitric Oxide—Induced Immunosensitization to Apoptosis by Fas-L and TRAIL -- Natural Agents That Can Sensitize Tumor Cells to Chemotherapy and Radiation Therapy -- Sensitization via Targeting Apoptotic Pathways -- Inhibitors of the Bcl-2 Protein Family as Sensitizers to Anticancer Agents -- Therapeutic Targeting of Apoptosis in Cancer -- Peptides and Peptidomimetics as Cancer Therapy Sensitizing Agents -- Non-Peptidic Mimetics as Cancer-Sensitizing Agents -- Sensitization of Cancer Cells to Cancer Therapies by Isoflavone and Its Synthetic Derivatives -- Antisense Oligonucleotides and siRNA as Specific Inhibitors of Gene Expression: Mechanisms of Action and Therapeutic Potential -- Sensitization Tailored to Individual Patients -- DNA Polymorphisms Affecting Chemosensitivity Toward Drugs -- Pharmacogenetics in Cancer Management: Scenario for Tailored Therapy.
Keywords: Cancer research; Oncology .; Pharmacology; Immunology; Cancer Research; Oncology; Pharmacology/Toxicology.; Immunology